A user centred design methodology for the development of technology in performance analysis of sport - Mooney, R.; Quinlan, L.; Olaighin, G. (Journal of Human Sport & Exercise, 2017)
There are a range of options available to sports scientists and coaches when choosing equipment for analysing athletic performance. However, dissatisfaction with a number of the most prominent systems currently available for the quantitative assessment of sports performance is limiting the extent to which quantitative analysis is taking place in applied settings (Mooney et al., 2015). The aim of this paper is to: (i) describe how a User Centred Design (UCD) methodology (Harte et al., 2014; Harte et al., 2015) can be used for development of novel systems for performance analysis in elite sport in order to address these issues and (ii) propose that this design approach may have application across a range of sports. A Use Case was developed that details the concept for a new technology and describes how the intended end users (sports scientists, coaches and athletes) will interact with the technology during the various stages of its operation. A Use Case is an interactive system analysis tool which can be viewed by various stakeholders and is an effective way of gathering and defining user requirements and establishing the context of use. Interviews with potential end users were conducted (N=41). Feedback from each interview was used to revise and update the Use Case in order to improve end user agreement with various aspects of the system design. Following multiple iterations of the Use Case, it was found that the final version received widespread acceptance from the study participants. 92.9% of total responses across all areas achieved positive feedback. Additionally, a score of 79.4 ±12.3 was achieved for the System Usability Scale, which can be regarded as above average (McLellan, Muddimer, & Peres, 2012). UCD is a framework of iterative processes, which facilitates the design of a product, service or method in a powerful manner to ensure that the usability of the device is maximised and that it satisfies user requirements. It is recommended that future sports technology development follows this UCD methodology in order to maximise end user satisfaction and increase the likelihood of the adoption of new technology into existing practices of analysing sports performance in applied settings.